Analisis Critical Thinking Siswa dengan Model Pembelajaran Numbered Head Together Materi Pecahan - Ulfatul Hasanah; Abdul Hamid; Firdaus Ainul Yaqin (IBTIDA', 2023)
The purpose of this research is to analyze students' critical thinking with the NHT learning model. This type of research is qualitative research. While the method used is descriptive method with research subjects in class V MIS Darul Hasan. Data were collected through observation, interviews, questionnaires, and critical thinking tests and analyzed by means of data classification, data reduction, data presentation, and drawing conclusions. The results showed that the students' Critical Thinking at MIS Darul Hasan was in the medium category with an average classical student score of 72,2 and experienced an increase of 22,2. Students in the high category think critically as much as 50%, students in the medium category as much as 22,2%, and students with critical thinking skills in the low category as much as 27,8%. Students who use the NHT model when studying fractional mathematics material are very capable of indicators of critical thinking making further explanations on sub-indicators of recognizing conjectures, and experiencing difficulties on indicators of critical thinking in formulating strategies and tactics on sub-indicators determining an action